PELAKSANAAN MANAJEMEN RISIKO DALAM MENGURANGI RISIKO CIDERA AKIBAT PASIEN JATUH DI RS X YOGYAKARTA - sundoro, totok; Firmansyah, Ramadhani (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Patients as users of health services have the right to obtain security and safety while undergoing treatment in hospital. Efforts to improve the quality of hospital services must be carried out through accreditation. Incidents of patient falls in hospitals will still occur in 2023. The research aims to determine regulations, implementation, obstacles and recommendations for implementing patient safety goals in reducing the risk of injury due to patient falls based on Hospital Accreditation Standards. Qualitative research with a case study research plan. The results are presented descriptively. The sampling technique used purposive sampling with 8 informants including 4 professional care providers and 4 patients. Data analysis uses the Miles and Hubermen analysis model by reducing data, presenting data and drawing conclusions. The results of the research show that policies and procedures have been established to reduce the risk of injury due to patient falls, all fall risk assessments are recorded in the patient's medical record and supporting facilities are available to reduce the risk of falls such as patient bells, hand rills, snaps on identity bracelets. patient. Several obstacles that need to be considered for improvement efforts are implementation that is not yet optimal and consistent as well as providing supporting facilities such as stickers and fall risk snaps which are often not available. So there is a need for regular monitoring and evaluation and management of logistics procurement for the need for supporting facilities in managing the risk of patient injury due to falls.